Preaching on the environment - Rolston, Holmes, 1932-2025, speaker; Cheng, Yang-en, speaker; Chen, Tzu-Mei, speaker; Chen, Yu-Ping, speaker; Unidentified speaker (Colorado State University. Libraries, 2016)
Rolston lecture at Taiwan Theological Seminary, Taipei, June 2, 2016. Biblical faith originated with a land ethic. Within the covenant, keeping the commandments, the Hebrew people entered a promised land. Nature is the creative, generative powers on Earth. Spirit is the animating principle that raises up life from the ground. Christian citizens ought to join others shaping a public environmental ethic. Earth is promised planet, planet with promise, sacred, holy ground.
Lecture given in English and translated in Mandarin.
To request a transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.
Keywords: nature; Promised Land; Jesus and nature; environmental policy; planet with promise; Bible; Earth; Judaism; Christianity